Diseño e implementación de un instrumento de gestión ambiental, seguridad y salud en el trabajo para el manejo de residuos peligrosos en el proceso de postventa del concesionario distribuidora mayorista de automóviles Madiautos S.A.S. (2016)
The degree work is to design and implement a management tool that enables the after-sales process WHOLESALE DISTRIBUTOR CAR dealership MADIAUTOS S.A.S. reduce the generation of hazardous waste. Hazardous waste is waste which possess toxicity, flammability, chemical reactivity, corrosivity, explosivity, reactivity, radioactivity that cause damage to human health and the environment. The sales process is responsible for performing the maintenance and repair of the vehicles it sells. These services includes arrangements in electrical engineering, sheet and painting which they derive hazardous waste, some associated with the activity itself (Used Oil, Fuels, Varsol) and other malpractices generated (solid, plushes, contaminated paper). Based on this problem it is to create a management tool from a diagnostic and input information on the current situation of the concessionaire The purpose of the tool is to train the staff shop sales in good environmental practices and health and safety work on the separation, storage and disposal of hazardous waste. This will help the process to properly manage waste and thus minimize those going to final disposal which represents an impact to the environment and risks that may affect the health of employees.